Thermophysical properties of different olive oils: Evaluating density and rheology through a fluid dynamic approach. Issue 7 (20th March 2017) - Ribeiro, Elisa Franco; Polachini, Tiago Carregari; Carvalho, Gisandro Reis; Romero, Javier Telis; Cabral, Renato Alexandre Ferreira
Abstract : The aim of this study was to investigate the Newtonian viscosity and density of different types of olive oils with the ultimate aim of optimizing the unit operations involved in their production process. A total of 14 oils were selected and tested at a wide range of temperatures. These included ten extra virgin olive oils (EVOOs) and four olive oils (OOs) from five different countries of origin. The oils were analyzed to determine their fatty acid (FA) composition and all were found to contain large amounts of monounsaturated FAs such as oleic acid. FA composition did not appear to influence density, but viscosity demonstrated slight differences in activation energy in accordance with monounsaturated (MUFA) and polyunsaturated fatty acid (PUFA) content. Both viscosity and density were affected by temperature. When the oils were heated, viscosity decreased exponentially following an Arrhenius type equation, while density decreased linearly. Rheological data was fitted well to theoretical results for absolute temperature and FA composition simultaneously, displaying fitting parameters different to those published in literature. A brief study of the fluid dynamics of the oils indicated close agreement between theoretical and experimental friction factor, confirming the accuracy of the prediction models reported in this work. Practical applications: If variations in fatty acid composition are not taken into account during olive oil production processes, problems could be encountered. In other words, over‐ or underestimating the liquid's dynamic properties could have adverse effects on pumping, refining, and other essential operations. This investigation therefore aimed to provide mathematical models to assess the thermophysical properties of various olive oils at a wide range of temperatures. Analyzing changes in density and dynamic viscosity provided valuable data that can be used to ensure equipment and processes are properly designed. The scarcity of fluid dynamic research in this specific area makes this investigation particularly relevant. Not only did it provide information about pressure loss in pipes and other parts of the machinery, it also proved useful in confirming the accuracy of prediction models reported by researching experimental density and rheological parameters. This work evaluated the fluid dynamic as a classical method to confirm the determination of the thermophysical properties of different commercial olive oils. Abstract : This work evaluated the fluid dynamic as a classical method to confirm the determination of the thermophysical properties of different commercial olive oils.